Kakra Singhi - A Potent Unani Drug for Respiratory Disorders (AYUSHDHARA, 2025)
Kakra Singhi (Pistacia integerrima J.L.Stewart), commonly known as Crab’s Claw, is a well-documented medicinal plant in Unani medicine, particularly valued for its effectiveness in managing respiratory disorders. Traditionally, it has been used in the treatment of cough, asthma, bronchitis, and other pulmonary conditions, owing to its potent Muqawwi (tonic), Munaffis-e-Balgham (expectorant), and Muhallil-e-Waram (anti-inflammatory) properties. The plant's galls, rich in flavonoids, tannins, alkaloids, and terpenoids, contribute to its bronchodilator, antihistaminic, and antitussive effects, making it a vital herbal remedy for respiratory ailments. Scientific studies have provided evidence for the anti-asthmatic, antihistaminic, and mast cell stabilizing activities of Kakra Singhi, demonstrating its ability to inhibit histamine release, suppress bronchospasms, and reduce inflammation in the airways. The methanolic extract of its galls has shown significant protection against histamine-induced bronchospasm, while the essential oil, containing alpha-pinene and beta-pinene, exhibits notable antibacterial and antioxidant properties, further supporting its role in respiratory health. Additionally, its anti-inflammatory action, mediated through cyclooxygenase and lipoxygenase inhibition, helps alleviate airway inflammation, making it a promising natural alternative in the management of chronic respiratory conditions. This review aims to present a comprehensive evaluation of the respiratory benefits of Kakra Singhi, bridging its traditional Unani applications with evidence-based scientific studies. By consolidating its phytochemical, pharmacological, and clinical findings, this article highlights its potential as a therapeutic Unani drug for respiratory disorders, encouraging further research and clinical validation.